Stem cell therapy for amyotrophic lateral sclerosis. Issue 1 (December 2015) - Mao, Zhijuan; Zhang, Suming; Chen, Hong
Abstract Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by the loss of motor neurons. Currently, no effective therapy is available to treat ALS, except for Riluzole, which has only limited clinical benefits. Stem-cell-based therapy has been intensively and extensively studied as a potential novel treatment strategy for ALS and has been shown to be effective, at least to some extent. In this article, we will review the current state of research on the use of stem cell therapy in the treatment of ALS and discuss the most promising stem cells for the treatment of ALS.